PENDAMPINGAN KOMUNIKASI ISLAM MAJELIS YASIN SEBAGAI MEDIA AGAMA DI TENGAH MASYARAKAT - Eka Fitri Qurniawati; Idawati Idawati; Fitri Almaidah; Sherena Ademia Lubis (Jurnal Pengabdian Kompetitif, 2026)
Development of Yasin Assembly Room as a Religious Media in the Community , This PKM activity is based on the problem faced by Partners, namely the mothers of the Yasin assembly in Mundam Village, Medang Kampai District, Dumai City, that this assembly is still perceived as a gathering place to meet each other in order to share information, so that some mothers feel that the impact is not too significant as a non-formal forum for studying religion. The activity was carried out in the form of Islamic Communication development in increasing Islamic insight skills for mothers in utilizing religious assemblies. The activity was carried out for the mothers of the Yasin assembly in Mundam Village, Medang Kampai District, Dumai City, lasted for approximately 3 hours, attended by 112 mothers who were members of the Yasin assembly , located in the mushalla Nurul Huda. The results of this activity provide assistance in the form of delivering material on Islamic values, and establishing a Yasin assembly space as a religious medium. The results obtained are able to form Islamic integrity based on behavior and noble morals, based on the characteristics of the Prophet Muhammad, Shiddiq, amanah, tabligh, fathonah. Strengthening the values of communication and Islamic brotherhood: Building solidarity and values of togetherness between the administrators and members of the Yasin assembly, living together, helping each other and working together. As well as having a logical understanding, having religious knowledge, far from traits, revenge, envy, and slander.